THE THEME OF MOTHERHOOD IN THE NOVEL "THE BIG HOUSE" BY MOHAMMED DIB - Karima Boukerch (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
Women’s personality has been central to the Arab narrative, with all its cultural and social affiliations. Arab novelists have employed multiple forms of women, perhaps most notably the personality of the mother, who has long been an engine and maker of events. In this intervention, however, we are interested in tracking the impact of motherhood in Mohammed Depp’s Big House novel. We note that there are four different forms of motherhood, and if they intersect in some of their statues, they differ in many respects, through the model of oppressed and neurological mothers or the model of vulnerable, good or injured mothers.